The Incredible hulk pop-up - Repchuk, Caroline (Marvel true believers retro character collection, 2008)
"Caught at the of a nuclear explosion mild-mannered scientist Bruce Banner is transformed by devastating gamma rays into the mighty, raging hulk..." --Back cover